Ocorrência e tratamento de monogenoides em alevinos de pampo (Trachinotus carolinus) cultivados experimentalmente na região norte do estado de São Paulo - Sanches, Eduardo G.; Ostini, Sergio; Rodrigues, Carolina Dos S. (Brazilian Coll Veterinary Parasitology, 2007)
This work had as objective tests therapeutic treatments seeking the monogenea eradication in fingerlings Florida Pompano (Trachinotus carolinus) servants in cage net in the area of Ubatuba, State of São Paulo. The fingerlings presented an accentuated weigh loss and strong discoloration and through observation of scraped of gills under light microscope were identified a high amount of monogenea. Three treatments were tested in form of baths: T1 (fresh water for 5 minutes); T2 (formalin: 1: 1.000 for 20 minutes) and T3: (formalin: 1:4.000 for 30 minutes). The treatments were appraised through scraped of gills, mounted among you laminate and laminulas and observed to the light microscope. It was observed that in the tested conditions all of the treatments were efficient in the elimination of the monogenea without presenting lethality to the fish. The treatment is recommended T I (take a bath in fresh water for 5 minutes) for the facility in the application and for the absence of use of chemical products.
Occurrence and treatment of monogenoides in fingerlings of florida pompano (Trachinotus carolinus) cultivated experimentally in the north area of the state of São Paulo
Keywords: monogenea; fluke; tratament; Trachinotus carolinus